Effect of Water Stress and Cutting Frequency on Alfalfa (Medicago sativa L.) Seed Production* - Ahmed, Mahmoud Fadlel Mula; Ahmed, Mohammed Sir El Khatim Sid (University of Khartoum Journal of Agricultural Sciences, 2023)
A split-plot experiment was conducted at the Demonstration Farm of the Faculty of Agriculture, University of Khartoum, during the period January 1999 - June 2000 to study the effect of water stress and cutting frequency on seed production of alfalfa (Medicago sativa L.). Three irrigation intervals (7, 14 and 21 days) were assigned to the main plots and designated I1 , I2 and I3 , respectively, and three cutting frequencies; namely, 21, 28 and 35 days were assigned to the subplots and given the symbols C 1 , C 2 and C 3 , respectively. Data were collected on number of racemes per plant, number of pods per raceme, number of seeds per pod, 1000-seed weight and final seed yield. Correlation analyses were carried out between yield and some of its components. The results revealed that shorter irrigation intervals (7 and 14 days) were significantly better than the longer interval (21 days), and the 35 days cutting frequency was the best for seed yield. Neither the number of seeds per pod nor the 1000-seed weight were affected by the cutting intervals. However, the former was significantly affected by irrigation intervals. Mean seed yield for the irrigation intervals was 77.9, 86.2 and 41,4 kg/ha for I1 , I2 and I3 , respectively. On the other hand, cutting frequencies resulted in seed yields of 38.1, 78,2 and 89.2 kg/ha for C 1 , C2 and C3 , respectively. Correlation analyses showed that seed yield was highly correlated with 1000-seed weight and number of seeds per pod.